The Influence of Inquiry Learning Model and Achievement Motivation on HOTS Economic Learning Outcomes on 11th Grade Students - Prima Lestari Situmorang; Indra Maipita; M. Fitri Rahmadana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims: (1) to know the difference between HOTS Economic learning outcomes taught by the Guided Inquiry learning model and the modified free inquiry learning model; (2) knowing the difference between HOTS Economic learning outcomes for students who have high achievement motivation and HOTS Economic learning outcomes for students who have low achievement motivation; and (3) knowing the interaction between inquiry learning models and achievement motivation on learning outcomes. The population in this study are all social studies 11th grade students in Senior High School 5 Medan, amounting to 3 classes. The sample in this study is determined randomly by random sampling technique, by taking 2 classes with a total of 34 students per class. The research method uses quasi-experimental. The instrument of this study is the achievement test and achievement motivation test. Analysis of the data used is Anvaa Factorial 2 x 2. Based on the research results obtained: (1) there are differences in the results of HOTS Economic student learning taught by the Guided Inquiry learning model and Guided Inquiry learning outcomes of students taught by the Modified Free Inquiry Learning Model (Modified Free Inquiry) with fcount>Ftable (4.15> 3.9); (2) there are differences in economic learning outcomes of students who have high achievement motivation and students who have low achievement motivation with fcount>Ftable (171.07> 3.9); (3) there is an interaction between inquiry learning models and achievement motivation on learning outcomes HOTS Economic with fcount>Ftable (4.04> 3.9).